Edukasi Kesehatan Gigi Untuk Mewujudkan Indonesia Bebas Karies 2030 - Rini, Willia Novita Eka; Herwansyah, Herwansyah; Wisudariani, Evy; Lanita, Usi; Ningsih, Vinna Rahayu (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2025)
Dental caries in children remains a significant public health problem in Indonesia, including in Jambi City. Based on data from the 2023 Indonesian Health Survey, the prevalence of caries in school-aged children reached over 40%, impacting quality of life, academic achievement, and the economic burden on families. Low knowledge and inappropriate tooth-brushing behavior are the main factors contributing to the high incidence of caries. The objective of this community service is to improve students' dental health knowledge and behavior, and to implement a professional collective toothbrushing program in elementary schools. This activity consisted of five stages: coordination with partners, dental health education, collective toothbrushing practice, mentoring, monitoring, and evaluation. The community service activity successfully improved children's knowledge about dental health and brushing skills.